PENGARUH FAKTOR MAKROEKONOMI TERHADAP PERTUMBUHAN EKONOMI INDONESIA PERIODE 2018-2020 - Anggit Dyah Kusumastuti; Annisa Indah Mutiasari; Destina Paningrum; Rusnandari Retno Cahyani (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2022)
This research aims to determine the effect of fundamental macroeconomic factors including inflation, the rupiah exchange rate and SBI interest rate on Indonesia economic growth before and during the covid-19 pandemic. The type of research is descriptive with a quantitative approach. The sample determination is based on quarterly time series data for the period January 2018 to December 2020 using the saturated sampling method, which consist of 12 samples. The simultaneous test result indicate that inflation, Rupiah exchange rate and SBI interest rate simultaneously effect on Indonesia economic growth. The partial test result, for inflation variable has a negative and significan effect on Indonesia economic growth. Meanwhile, the Rupiah exchange rate and the SBI interest rate has a negative but not significant effect on Indonesia economic growth. Efforts to control inflation, stablize exchange rate and interest rate through optimizing the use of domestic products, improving export performance, such as reducing export tariffs and restricting imports of goods.